Territory marketing of tourist destination. (Journal of Economic Research & Business Administration, 2015)
In this article the authors made a report about the possibility of creation of competitive tourist product in the different types of tourism on the base of tourist potential in Akmola region which will be high de a region which will be high demanded by different groups of consumers under the well-formed organization of territory marketing. The conducted marketing of territories in Akmola region defined the necessity of systematization of tourist potential by the principle of zoning. The major aim is to create the conditions for organized mass tourism and rest, long staying and excellent service of guests. The main tasks of TRA: to increase the effectiveness of region tourist potential usage, conservation of natural landscape, biodiversity of flora and fauna and its use in the perspectives of organized tourism; preservation of cultural heritage and its use in the perspectives of organized tourism; increase of tax proceedings from tourist activity to budget of all levels; creation of conditions for realization of investment projects, providing inflow of investments and creation of new jobs; social welfare and providing comfort environment for living of people who lives in this region; assistance for physical, moral, authentic, patriotic education of nationals. Creation of TRA allows increasing the investment attractiveness of territory.
Keywords: territory marketing; tourist destination; tourist resources; tourist recreation areas; Akmola region